Studi Litelatur Analisis Komponen Biomotor Utama Permainan Bolavoli Indoor - Napoleon Adi Nugroho Joyokusumo; Soni Sulistyarto; Dbolavolir. Andun Sudijandoko; Noortje Anita Kumaat (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
Understanding the biomotor components in sports is essential in competitive sports, especially volleyball. This is because many athletes in the non-elite category do inappropriate training programs due to a lack of knowledge of the specific needs of biomotor components in volleyball, so the training program is ineffective. This study aims to provide an understanding of the main biomotor components that need to be developed through the right training program to support maximum performance in volleyball. The research method uses the context review method, a common form of review in literature studies quoted from relevant research results. This study examines the results of previous studies quoted from international journals such as ScienceDirect, PubMed, and journals from various universities in Indonesia. Based on the research results, the main biomotor components in volleyball are strength, speed, endurance, explosive power, flexibility, and coordination as well as agility and balance.